ANALISIS BESARAN UPAH DALAM MENINGKATKAN KESEJAHTERAAN KARYAWAN HARIAN LEPAS PADA PT. GUNTA SAMBA - Ali; Aji Ratna Kusuma; Rizkiawan (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2020)
The purpose of this study was to examine and analyze the amount of wages provided by the company to improve the welfare of daily casual employees in accordance with this study entitled